Food Wastes (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Food is a precious commodity and its production can be resource-intensive. According to the Food and Agriculture Organization of the United Nations, nearly 1.3 billion tons of food products per year are lost along the food supply chain, and in the next 25 years, the amount of food waste has been projected to increase exponentially. The management of food waste should follow certain policies based on the 3Rs concept, i.e., reduce, reuse, and recycle. Currently, most food waste is recycled, mainly as animal feed and compost. The remaining quantities are incinerated and disposed in landfills, causing serious emissions of methane (CH4), which is 23 times more potent than carbon dioxide (CO2) as a greenhouse gas and significantly contributes to climate change. Valorizing food waste components could lead to numerous possibilities for the production of valuable chemicals, fuels, and products. The present Special Issue compiles a wide spectrum of aspects of research and technology in the area of food waste exploitation, highlighting prominent current research directions in the field for the production of value-added products such as polylactic acid, hydrogen, ethanol, enzymes, and edible insects.